Analysis of Islamic Banks’ Merger in Indonesia - Fitri Mareta; Heliani Heliani; Siti Elisah; Andini Ulhaq; Indri Febriani (Universitas Tidar, 2021)
Islamic bank is a bank that collects funds from the public by using system profit sharing for every profit it gets and in carrying out its activities in accordance with Islamic law. Remembering that in Indonesia most of the population is Muslim, therefore they need a bank that works in accordance with Islamic law. Considering the number of percentages of Islamic banks in Indonesia are still small and cannot yet dominate the market share, therefore this research is expected to find out whether the merging of 3 Islamic banks (BRIS, BSM and BNIS) able to control market share or not. To see the synergy resulting from this merger is used methods Discounted Cash Flow - Free Cash Flow to Equity and Relative Valuation - Price to Book Ratio. The data used are the financial statements of each bank from 2014 to 2019 which are available on the Indonesia Stock Exchange (IDX) or the websites of each bank.